Clinical Outcome After Pencil Beam Scanning Proton Therapy of Patients With Non-Metastatic Malignant and Benign Peripheral Nerve Sheath Tumors - Bachmann, Nicolas; Leiser, Dominic; Pica, Alessia; Bachtiary, Barbara; Weber, Damien C. (Frontiers in Oncology, 2022)
Objective: Peripheral nerve sheath tumors (PNSTs) commonly arise from peripheral nerve roots and grow locally invasive. Malignant PNSTs (mPNSTs) represent aggressive sarcomas of neural origin that can originate from PNSTs. Radiation therapy is commonly used as part of the required multimodal treatment. However, both entities tend to occur early in life and are associated with the genetic disorder neurofibromatosis type 1 (NF-1), which is known to cause increased radiosensitivity. Pencil beam scanning proton therapy (PBSPT) allows for a minimization of dose delivered to organs at risk and the integral dose and, thus, potentially also a reduction of radiation-induced adverse events. We report the clinical outcome and toxicity rates of patients with (m)PNSTs treated with PBSPT. Methods: We retrospectively reviewed 36 patients who received PBSPT (median dose, 64 GyRBE) with curative intent for (m)PNSTs between 1999 and 2020 at our institute. Twenty-eight (78%) and 8 (22%) patients were treated at diagnosis and for tumor recurrence/progression, respectively. Median age was 32 years (range, 3 – 75) and 25 (69%) patients were male. mPNST and PNST were diagnosed in 31 (86%) and 5 (14%) patients, respectively. Underlying NF-1 disease was found in 8 (22%) patients. Acute and late toxicities were recorded according to CTCAE v4.1. Overall survival (OS), local control (LC), and distant control (DC) were estimated using the Kaplan-Meier method. Results: With a median follow-up time of 31 months (range, 4 – 194), 13 (36%) patients died with progressive disease, 8 (22%) experienced local failure and 14 (39%) distant failure after PBSPT. Estimated 2-year OS, LC and DC was 75.5%, 73.5% and 61.2%, respectively. Acute grade 3 toxicity (dermatitis, mucositis, pain) was observed in 5 (14%) patients. Late grade 3 cataract and osteonecrosis were both observed in 1 (3%) patient, 34 and 194 months after PBSPT, respectively. There was no late grade >3 toxicity or radiation-induced secondary cancer. Conclusion: To our knowledge, this is the first study to analyze the outcome of (m)PNSTs treated with proton therapy using a PBS delivery paradigm. In our cohort, consisting mainly of patients with mPNSTs, we report reasonable oncological outcomes and low toxicity rates after PBSPT.